Proteins at interfaces - Evers, Florian (Technische Universität Dortmund, 2011)
Protein adsorption is a fundamental and ubiquitous phenomenon, which has severe implications in the fields of biomaterials as well as bio- and nanotechnology, e.g., in drug delivery, biofouling, the biocompatibility of implants, food chemistry, and biosensors. Therefore, the mechanisms of protein adsorption and controlling the interfacial affinity of proteins have become intriguing and interdisciplinary research topics. In this work, X-ray and neutron reflectometry are the main techniques applied to study protein adsorption. Thus, the interfacial structure of adsorbed protein films can be characterized in terms of film thickness, protein volume fraction inside the adsorbed layer, and adsorbed amount. The four main achievements of this thesis are summarized as follows: - In comprehensive studies, the potential of osmolytes to reduce protein adsorption has been revealed. For three functionally different model interfaces, it is shown that adding nonionic cosolvents to protein solutions leads to a decreased surface excess of proteins by lowering the protein packing density inside the adsorbed protein layer. Hence, these results provide a means to control the interfacial affinity of proteins. - Furthermore, the addition of ionic cosolvents to protein solutions alters attractive and repulsive electrostatic interactions between proteins and surfaces as well as between proteins inside the adsorbed layer. In the presence of NaCl, protein adsorption at hydrophobic surfaces can be increased, whereas the presence of kosmotropic and chaotropic salts leads to reduced protein adsorption. In particular, this study addresses Hofmeister effects on protein adsorption. - Polyelectrolyte brushes are an interesting tool to control non-specific protein adsorption. In this work, the properties of a poly(acrylic acid) brush in the presence of insulin are analyzed. It is shown that poly(acrylic acid) brushes can provide a biocompatible environment even for aggregation-prone peptides. - Moreover, the influence of surface chemistry and substrate composition on protein adsorption is analyzed. It is clearly shown that protein adsorption at hydrophobic surfaces can lead to drastic conformational changes of adsorbed proteins, and that van der Waals forces exert significant effects on protein adsorption.
Protein adsorption studied by X-ray and neutron reflectometry
Keywords: Protein adsorption; Surface functionalization; X-ray reflectometry; Neutron reflectometry; Cosolvent; Hofmeister effect; Polymer brushes; Self-assembled monolayers; 530